On Nonreductive Biography and Eternal Self-Overcoming (Lyuty, Т. Nietzsche. Self-Overcoming. Кyiv: Tempora, 2016) - Menzhulin, Vadim (Sententiae, 2017)
The publication of Taras Lyuty’s book of Nietzsche is a salient event in the philosophical life of Ukraine in 2016. Given the fact that the book covers a great number of different issues, the reviewer decides to focus on those of them which correspond to his own academic interests, related primarily to the history of psychoanalysis and biographical approach within the historiography of philosophy. As it is shown on the review, Lyuty masterfully avoids such a trap as biographical reductionism. He neither reduces his hero’s teaching to his life, nor isolates the former from the latter. The reviewer pays a special attention to Lyuty’s delineation of intellectual links between the great philosopher and some of his predecessors (such as Ralf Waldo Emerson) and followers (some pioneers of depth psychology). In the end, the reviewer demonstrates that a very deep and systematic analysis of Nietzsche’s biography and philosophical heritage carried out by Lyuty leaves a room for further productive reflections and interpretations.